HALLUCINATION IN PATIENTS WITH BORDERLINE PERSONALITY DISORDER - Nico Savero; Aulia Pandu Aji; Avicenna Hanan Alim; I Made Bagus Suryananda; Ruth Clarita Pradibdo; Happy Indah Hapsari; Dearisa Surya Yudhantara (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
In modern practice, hallucinations found in patients with borderline personality disorder (BPD) are often identified as â€˜pseudohallucinationsâ€™ to state the suspicion that they do not qualify as true hallucinations. In the interest of Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria for BPD, it is stated that during times of tremendous stress, transient ideation of paranoid or dissociative symptoms may occur. BPD is defined as a mental health disorder with remarkable impulsivity, instability of mood and interpersonal relationships, along with suicidal behavior that can complicate medical treatment. It is crucial to identify this diagnosis to plan for further treatment. The existence and severity of hallucinations in BPD patients are closely related to posttraumatic stress disorder (PTSD), prior childhood adversities, as well as current adult life stressor. Auditory verbal hallucinations (AVH) were reported to be the most commonly observed types of hallucinations in patients with BPD. Similarities of the AVH characteristics between BPD patients and those with schizophrenia make it hard to diagnose and manage the hallucinations in BPD patients. Pharmacological management including both typical and atypical antipsychotic drugs may be beneficial in order to treat hallucinations in these patients, however, low-dose antipsychotics are preferred due to its adverse reaction. Psychotherapy such as cognitive behavior therapy (CBT) and non-invasive brain stimulation techniques may be helpful as well. Questioning patientâ€™s psychotic symptoms in an untrue or â€œmade-upâ€ form is rarely advantageous and may leads to undesired therapeutic alliance dismissal.Â Keywords: hallucination, borderline personality disorder, depression.